2021
DOI: 10.3390/fib9090053
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive Yb-Doped Germanophosphosilicate Artificial Rayleigh Fibers as a Base of Random Lasers

Abstract: Asingle-mode Yb-doped germanophosphosilicate fiber with ultra-low optical losses (less than 2 dB/km) was fabricated by means of the MCVD method utilizing an all-gas-phase deposition technique developed “in house”. The absorption and luminescent spectral properties of the fiber were thoroughly studied. The photosensitivity of the pristine (non-hydrogenated) fiber to 248 nm-laser radiation was confirmed by means of fiber Bragg grating (FBG) inscription directly during the drawing process. The random single-frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This behavior and the oscillation frequency value, however, are typical for Er-doped fiber lasers and it was It was also found that the studied laser operated strictly in a continuous-wave (CW) mode, without any self-pulsing (such as a Q-switch). This result is in good agreement with our previous works [19][20][21][22]25]. The CW laser operation can be explained by the contribution of the dynamic grating formation [19,20].…”
Section: Pump Power Mwsupporting
confidence: 92%
See 1 more Smart Citation
“…This behavior and the oscillation frequency value, however, are typical for Er-doped fiber lasers and it was It was also found that the studied laser operated strictly in a continuous-wave (CW) mode, without any self-pulsing (such as a Q-switch). This result is in good agreement with our previous works [19][20][21][22]25]. The CW laser operation can be explained by the contribution of the dynamic grating formation [19,20].…”
Section: Pump Power Mwsupporting
confidence: 92%
“…Thus, provided that the operating frequency range is within the reflection spectrum of the gratings, OFs with an FBG array are a good alternative to traditional Rayleigh fibers and, therefore, called "artificial Rayleigh fibers". In particular, they can be effectively used in such applications as coherent reflectometry [15,16] and random lasers [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%